Different roles of interleukin 6 and interleukin 11 in the liver: implications for therapy - Anissa A. Widjaja; Sonia P. Chothani; Stuart A. Cook (Taylor & Francis Group, 2020)
The interleukin 6 (IL6) family of proteins regulate important cellular processes and act through a variety of signaling pathways via a shared gp130 receptor. In the liver, there is a large body of evidence showing a protective and pro-regenerative role for IL6 cis and trans signaling. While a few studies suggest a pathological role for IL6 trans-signaling in the liver. IL11 is often thought of as similar to IL6 and redundancy has been inferred. However, recent studies reveal that IL6R and IL11RA are expressed on dissimilar cell types and these cytokines actually have very different roles in biology and pathology. In the liver, IL6R is mostly expressed on immune cells, whereas IL11RA is highly expressed on hepatocytes and hepatic stellate cells, both of which exhibit autocrine IL11 activity. In contrast to the beneficial effects of IL6 in the liver, IL11 causes liver disease and its expression in stromal and parenchymal cells leads to fibrosis, inflammation, steatosis and hepatic failure. In this review, we address IL6 and IL11 in the context of liver function. We end by discussing the possibility of IL6 gain-of-function versus IL11 inhibition as therapeutic approaches to treat liver disease.,